Religion and institutions - Mrdjan M. Mladjan; Elena Nikolova; Olga Ponomarenko (Global Labor Organization (GLO), 2024)
Institutions, defined as "the rules of the game in society", drive economic growth and prosperity. Institutions often arise from long-term processes influenced by geography, major historical events, culture, and, less commonly, religion. This chapter reviews the available evidence to demonstrate that religion has a strong effect on formal (laws, judicial and financial systems, contract enforcement) and informal (traditions, taboos, codes of conduct) institutions. Church-state relationships hundreds of years ago affect informal institutions like work ethic, preferences for rationality or spirituality, and attitudes towards innovation. In terms of formal institutions, there is evidence of causal effects of religious doctrines on institutions such as democratic government, independent courts, private property, or inheritance rights. Moreover, there is evidence that formal and informal institutions also influence religious institutions and doctrines. The chapter also reviews the theories of religious markets and secularization to conclude that neither of them are well positioned to predict how the relationship between religions and institutions will unfold in the future. The chapter then enumerates several empirical challenges inherent in the study of religion and institutions, and proposes way to overcome them. It also suggests several fruitful areas for future research, including using more fine-grained data and developing new theoretical tools, identifying mechanisms through both quantitative and qualitative data, and expanding the research focus beyond Christian denominations in order to focus on non-Western religions.
Keywords: Z12; D02; O43; 330; religion; institutions; culture